(untitled) (Research, Society and Development, 2022)
Spontaneous extrahepatic bile duct perforation is a rare cause of cholestasis in childhood in which the diagnosis is often only determined through exploratory laparotomy and the acute clinical presentation is uncommon. The prognosis is good when diagnosed early. Objective: to report the case of spontaneous bile duct perforation in an infant and its possible complications after surgical treatment. Case report: A 2-month-old infant who developed progressive weight loss associated with fecal acolia, intermittent choluria and abdominal distension for 1 month. Laboratory tests showed increased transaminases with normal liver function. Abdominal USG showed voluminous ascites, performed paracentesis with drainage of bilious fluid. Percutaneous cholangiography showed possible perforation at the level of the common bile duct, laparotomy was performed; Extrahepatic bile duct perforation was found, cholecystectomy and simple bile duct raffia were performed. In the postoperative study, at 8 months, the patient developed upper digestive hemorrhage secondary to esophageal varices due to portal vein thrombosis; needed treatment with vasopressin in the acute setting and follow-up with serial sclerotherapy associated with the established clinical treatment. Comments: Biliary perforation is a rare condition that makes it a diagnostic and therapeutic challenge. The prognosis will depend on early intervention and intraoperative findings.